2018
DOI: 10.31524/bkkmedj.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Potential Skin Sensitization and Collagen Synthesis of Rats Receiving Proteoglycan Serum

Abstract: The aim of this study is to evaluate potential skin sensitization and collagen synthesis on the skin of rats receiving PG serum extracted from fish (Trichopoduspectoralis) in vivo model. Abstract OBJECTIVE:The aim of this study was to evaluate potential skin sensitization and collagen synthesis of rats receiving proteoglycan (PG) serum. MATERIAL AND METHODS: Eighteen rats were randomly divided into 3 groups equally and assigned to receive 1 ml of serum base (control), 1% PG and 2% PG applied to skin. Histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This study was investigated using the method of Chuenwattana et al (2018). 3 Skin tissue sections were deparaffinized in xylene, hydrated, and stained in Weigert's iron hematoxylin solution for 10 minutes. They were washed and stained in acid fuchsin solution for 3 minutes, rinsed in distilled water, treated with phosphomolybdicphosphotugstic acid solution for 15 minutes, immediately submerged into aniline blue solution for 10 minutes, rinsed in distilled water, treated with acetic solution for 10 minutes, dehydrated in 95% alcohol, cleared twice in xylene, mounted with a cover slip, and observed under a light microscope.…”
Section: The Masson's Trichrome Examinationmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was investigated using the method of Chuenwattana et al (2018). 3 Skin tissue sections were deparaffinized in xylene, hydrated, and stained in Weigert's iron hematoxylin solution for 10 minutes. They were washed and stained in acid fuchsin solution for 3 minutes, rinsed in distilled water, treated with phosphomolybdicphosphotugstic acid solution for 15 minutes, immediately submerged into aniline blue solution for 10 minutes, rinsed in distilled water, treated with acetic solution for 10 minutes, dehydrated in 95% alcohol, cleared twice in xylene, mounted with a cover slip, and observed under a light microscope.…”
Section: The Masson's Trichrome Examinationmentioning
confidence: 99%
“…The study demonstrated that this serum has accelerated collagen synthesis and low potential skin sensitization in rat models. 3 In 2019, Bunman developed and formulated a new cream for facial use, called "bright and firm hybrid emulsion I". Bright and firm hybrid emulsion I is composed of many active ingredients such as pseudoalteromonas ferment extract, chlamydomonas extract, hamamelis virginiana (witch hazel) extract, and astaxanthin etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation